2013
DOI: 10.1111/tpj.12368
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor HAT1 is phosphorylated by BIN2 kinase and mediates brassinosteroid repressed gene expression in Arabidopsis

Abstract: SUMMARYPlant steroid hormones, brassinosteroids (BRs), play essential roles in modulating cell elongation, vascular differentiation, senescence and stress responses. BRs signal through plasma membrane-localized receptor and other components to modulate the BES1/BZR1 (BRI1-EMS SUPPRESSOR 1/BRASSINAZOLE RESISTANT 1) family of transcription factors that modulate thousands of target genes. Arabodopsis thaliana homeodomain-leucine zipper protein 1 (HAT1), which encodes a homeodomain-leucine zipper (HD-Zip) class II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 73 publications
(121 reference statements)
4
97
0
Order By: Relevance
“…Numerous BIN2/GSK2 substrates were identified in recent years, including a number of transcription factors (Vert et al, 2008;Ye et al, 2012;Zhang et al, 2012Zhang et al, , 2014aZhang et al, , 2014bCho et al, 2014), suggesting that the negative regulator BIN2/GSK2 acts as the central player in the BR response, similar to most other hormone-signaling pathways (Huq, 2006). Our analysis combined with previous reports implied that these transcription factors, (A) Physiological BR induces GA biosynthesis, inhibits GA inactivation, and stimulates self-biosynthesis to promote cell elongation.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous BIN2/GSK2 substrates were identified in recent years, including a number of transcription factors (Vert et al, 2008;Ye et al, 2012;Zhang et al, 2012Zhang et al, , 2014aZhang et al, , 2014bCho et al, 2014), suggesting that the negative regulator BIN2/GSK2 acts as the central player in the BR response, similar to most other hormone-signaling pathways (Huq, 2006). Our analysis combined with previous reports implied that these transcription factors, (A) Physiological BR induces GA biosynthesis, inhibits GA inactivation, and stimulates self-biosynthesis to promote cell elongation.…”
Section: Discussionsupporting
confidence: 54%
“…HAT1 and HAT3 are positive regulators for BR-regulated growth as double mutants of hat1 hat3 have reduced BR response in hypocotyl elongation assays and overexpression of HAT1 leads to increased stem elongation at the early stage of vegetative growth. 30 We further found that HAT1 binds to a conserved DNA binding site (TAATAATTA), interacts with BES1 bound to BRRE site to cooperatively inhibit BR-repressed gene expression. The results suggest that HAT1 function as a co-repressor of BES1, providing a mechanism for BES1 to repress gene expression.…”
mentioning
confidence: 99%
“…The results suggest that HAT1 function as a co-repressor of BES1, providing a mechanism for BES1 to repress gene expression. 30 Interestingly, HAT1 has more than 20 putative phosphorylation sites for BIN2 kinase and is phosphorylated by BIN2 kinase in vitro and likely in vivo as well. 30 Unlike BIN2 phosphorylation of BES1/ BZR1, BIN2 phosphorylation appears to stabilize HAT1 protein, 30 which is similar to BIN2 phosphorylation of MYBL2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The unphosphorylated BES1 and BZR1 prefer to bind E-boxes (CANNTG) and/or BR response elements (CGTG T / C G) to regulate target gene expression (He et al, 2005;Yin et al, 2005). Furthermore, BES1 interacts with basic helix-loophelix (bHLH) transcription factors BIM1-3, histone demethylases ELF6 and REF6, histone methyltransferase SDG8, MYB family transcription factor AtMYB30, corepressors MYBL2, HAT1, and TPL-HDA19, and transcription elongation factor IWS1 to regulate gene expression (He et al, 2005;Yin et al, 2005;Yu et al, 2008;Li et al, 2009Li et al, , 2010Ye et al, 2012;Ryu et al, 2014;Zhang et al, 2014). Genome-wide studies have revealed that the BES1/BZR1 family regulates a transcription network involving thousands of genes (Sun et al, 2010;Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%